ANALISIS KESULITAN MENULIS KALIMAT EFEKTIF SISWA KELAS III DI SD MUHAMMADIYAH JONGAYA - Awaliyah, Feby Rezky; Aco Karumpa; Muhammad Saeful (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing is one of the important language skills that must be mastered by elementary school students, especially in writing effective sentences. However, in practice many students still experience difficulties in constructing sentences that follow the rules of the Indonesian language. This study aims to analyze the difficulties in writing effective sentences among third grade students of SD Muhammadiyah Jongaya. This research used a descriptive qualitative approach. The subjects of this study were the third grade students of SD Muhammadiyah Jongaya, with the class teacher as an additional informant. Data were collected through observation, writing tests, interviews, and documentation. The data obtained were then analyzed qualitatively to describe the forms of difficulties experienced by students in writing effective sentences. The results of the study indicate that third grade students of SD Muhammadiyah Jongaya experience several difficulties in writing effective sentences, including difficulties in the use of spelling and punctuation, selecting appropriate words, arranging sentence structure, and developing ideas into complete and clear sentences. The factors causing these difficulties include limited vocabulary, lack of understanding of language rules, and limited continuous writing practice. Therefore, more varied and continuous learning efforts are needed to improve students’ writing skills in constructing effective sentences.